Analisis Afiksasi dalam Surat Kabar Serambi Indonesia Edisi 8 Desember 2023 - Hafni, Nurul; Boangmanalu, Anisa; Serliana, Indri; Nurazizah, Nurazizah; Solihat, Qonita; Syuhuri, Saiyidatu; Istiqamah, Istiqamah; Sundana, Lina (Multiverse: Open Multidisciplinary Journal, 2024)
This study explores the morphological process of affixation as a core mechanism in language formation, specifically within the context of the Serambi Indonesia newspaper, 2023 edition. Affixation refers to the addition of morphemes—prefixes, infixes, suffixes, confixes, and simulfixes—to root words, thereby creating new lexical forms and meanings. The research investigates how these affixation forms contribute to word formation and grammatical function in written media. Employing a qualitative descriptive methodology, the study involves collecting linguistic data from news articles and systematically categorizing the affixes based on their types and structural roles. The main research question centers on identifying the patterns and frequency of affixation used in the selected texts. The findings reveal that five types of affixation are present: seven prefixes, one infix, four suffixes, two confixes, and two simulfixes. These results highlight the dynamic role of morphological processes in media discourse, offering insights into how affixation operates not only as a grammatical tool but also as a stylistic and semantic enhancer in journalistic language. The study concludes that affixation plays a crucial role in shaping the richness and variability of the Indonesian language as used in contemporary media.